2012
DOI: 10.1177/0022343311431286
|View full text |Cite
|
Sign up to set email alerts
|

Can states buy peace? Social welfare spending and civil conflicts

Abstract: This study examines whether the state's ability to provide social welfare services has any major effect on the probability of civil conflict onset. We argue that welfare spending contributes to sustaining peace because the provision of social services reduces grievances by offsetting the effects of poverty and inequality in society. Welfare spending serves as an indication of the commitment of the government to social services and reflects its priorities and dedication to citizens. By enacting welfare policies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 73 publications
3
92
0
Order By: Relevance
“…31 As noted by Halaby (2004:511), the random effect estimator is strongly influenced by cross sectional variance and underlies the assumption that unobserved heterogeneity is mean independent from the causal variable. 32 The choice of this time period was contingent on the availability of the welfare spending data from Taydas and Peksen (2012). 33 Regarding the control variables, per capita GDP is negatively associated with welfare spending, which is in line with previous findings (Ha 2008;Rudra and Haggard 2005).…”
Section: Resource Ownership Patterns and Welfare Spendingsupporting
confidence: 65%
See 2 more Smart Citations
“…31 As noted by Halaby (2004:511), the random effect estimator is strongly influenced by cross sectional variance and underlies the assumption that unobserved heterogeneity is mean independent from the causal variable. 32 The choice of this time period was contingent on the availability of the welfare spending data from Taydas and Peksen (2012). 33 Regarding the control variables, per capita GDP is negatively associated with welfare spending, which is in line with previous findings (Ha 2008;Rudra and Haggard 2005).…”
Section: Resource Ownership Patterns and Welfare Spendingsupporting
confidence: 65%
“…Indeed, some authors show that natural resources such as hydrocarbons may increase social spending and internal stability (Morrison 2008). Welfare spending is found to reduce the probability of civil war onset (Taydas and Peksen 2012), and NOCs, in particular, are believed to support the building of strong welfare states (Marcel and Mitchell 2006). Furthermore, hydrocarbons are often employed when building up a large military apparatus and deploying coercion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Results from quantitative studies point in different directions: while some authors have found a negative or curvilinear effect (e.g. Collier and Hoeffler, 2004;Ellingsen, 2000;Reynal-Querol, 2002), others have shown that fractionalization is positively associated with internal violence (Schneider and Wiesehomeier, 2008;Taydas and Peksen, 2012). A third group of scholars has found no relationship between ethnic fractionalization and armed conflicts (Fearon and Laitin, 2003;Østby et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Schneider and Wiesehomeier (2008) find that fractionalization can be linked to low-intensity intrastate conflicts in democracies (whereas this effect is insignificant for pure autocracies). A recent analysis by Taydas and Peksen (2012) finds a positive and significant association between ethnic fractionalization and civil conflict.…”
mentioning
confidence: 98%